2004
DOI: 10.1016/j.clinbiochen.2003.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The paraoxonase promoter polymorphism (−107)T>C is not associated with carotid intima-media thickness in Sicilian hypercholesterolemic patients

Abstract: Background and Objectives: Increased plasma low-density lipoprotein-cholesterol (LDL-C) levels in hypercholesterolemic subjects are associated with enhanced LDL oxidation that represents an additional risk for atherosclerotic disease. Human serum paraoxonase (PON1), a high-density lipoprotein (HDL) associated enzyme, has been shown to protect LDL from oxidation, thus playing an important role in reducing the risk of atherosclerosis. PON1 gene polymorphisms have been found to be associated with the variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…It was noted that the Q192R polymorphism of PON1 was not related to carotid intima thickness (127). A similar result was reported for Sicilian hypercholesterolemic patients in whom early carotid atherosclerosis and polymorphism were found unrelated (128). These results were confirmed by the findings of the EPIC Norfolk study group who did not find any correlation between the cardiovascular system and Q192R variants (129).…”
Section: Effects On Cardiovascular Systemsupporting
confidence: 80%
See 1 more Smart Citation
“…It was noted that the Q192R polymorphism of PON1 was not related to carotid intima thickness (127). A similar result was reported for Sicilian hypercholesterolemic patients in whom early carotid atherosclerosis and polymorphism were found unrelated (128). These results were confirmed by the findings of the EPIC Norfolk study group who did not find any correlation between the cardiovascular system and Q192R variants (129).…”
Section: Effects On Cardiovascular Systemsupporting
confidence: 80%
“…For instance, while the 55M allele was found to be in high frequency in the Portuguese (130), Germans (125) and Taiwanese (122), the L variant was found more common in Italians (120,127) and Brazilians (131). Despite all these findings, Campo et al (128) reported that there was no correlation between the L55M polymorphism and the cardiovascular system. Studies conducted on the Turkish population demonstrat ed that there might be a relation between PON1, Q192R gene polymorphism and coronary artery diseases (132 ).…”
Section: Effects On Cardiovascular Systemmentioning
confidence: 65%
“…Similar to HDL-C, the contribution of paraoxonase to IMT is debatable. Some studies have reported a significant association between PON1 and IMT in FH patients (9), in middle-aged women (34), and in a subgroup of nonsmokers (35), but there are also a number of reports, including the current one, that did not find an association between PON1 and IMT (30,(36)(37)(38). These differences in outcome suggest that there is only a weak relation between PON1 and IMT that will not be observed in many small studies that lack the power to detect weak effects.…”
Section: Discussionmentioning
confidence: 66%
“…Remarkably, several studies, including ours, did not observe a significant relation between HDL-C and CCA-IMT (30)(31)(32)(33). Apparently, HDL-C has only minor effects on CCA-IMT.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, lower serum PON1 lactonase and arylesterase activities are associated to metabolic alterations related to childhood overweight and onset and/ or development of diabetes and CVD later in life [1,5]. Nevertheless, data on the relationship between PON1 and nutritional status as well as lipid profile in childhood are limited and sometimes controversial, mainly due to differences in measurement techniques and data analysis [13,14]. Such situation is expected to be clarified by the analysis of the interaction between gene, PON1 arylesterase activity, and nutritional status.…”
Section: Introductionmentioning
confidence: 99%